An Implementation of Service Composition for Enterprise Business Processes. (February 2019) - Ke, Jian; Xu, Jian Bo; Feng, Shu
Abstract: The Microservice Architecture (MSA) is an advanced architecture with flexible technology selection, independent on-demand expansion, and high availability. It is one of the best solution for enterprise software systems to cope with cloud deployment. Moreover, Spring Cloud provides comprehensive technical support for microservice architecture; also, it is the best technical framework for implementing microservice architecture. The container technology represented by Dockers provides an independent and undisturbed deployment environment for microservice architecture. Based on the microservice architecture and lightweight container technology, this article propose an implementation idea for service composition.